The Epistemology of Quraish Shihab’s Interpretation of Poverty in Tafsir Al-Misbah - Moh. Nurun Alan Nurin PK. (Indonesia); Thomas K. Gugler (Frankfurt, Jerman); Ali Miqdad Ali (Malete, Nigeria); Mila Aulia Hamdan (Indonesia) (IAT IAIN Pontianak, 2023)
This study departs from the interpretation of M. Quraish Shihab on poverty verses. as an effort to verify and validate the truth of the interpretation of poverty in Tafsir Al-Misbah, this study seeks to review the epistemological aspects of Quraish Shihab's interpretation in Tafsir Al-Misbah on poverty verses. This study can be classified as a qualitative study. This research is included in descriptive-analytical research. Called descriptive because this study will review and analyze the Quraish Shihab Interpretation of the verses of Poverty in Tafsir Al-Misbah. The results of this study are, First, the source of interpretation, the interpretation set forth in Tafsir Al-Misbah, especially with regard to the verses of Shikinan in the Qur 'an, can not be separated from the principles that prioritize Sahihic histories and the context of the relationship between one verse and another (read : munasabatul ayat), as well as how the background of the verse then pours out the meaning that is relevant to the context today. Second, Methodology of interpretation, Tafsir Al-Misbah as a contemporary tafsir work tends to use analytic methodology (tahlily) in revealing the message and meaning contained in a verse. More specifically in the context of the poverty verses of Quraish Shihab as a mufassir it is very visible how the interpretive effort is very thick with cultural and societal literary styles (al-adabi al-ijtima 'i), and the third aspect is the validity of interpretation, with reference to several aspects, coherence, correspondence, and pragmatism. That M. Quraish Shihab's interpretation of the scriptures is very appropriate and has a strong relevance to the phenomenon of poverty that occurs, besides that the interpretation presented is not only pouring meaning in the Qur'an but also presents a problem solver to the phenomenon and reality that occurs. When drawn in the context of M. 's interpretation. Quraish Shihab in the tafsir ofAl-Misbah which specifically discusses the term poverty in the Qur'an can be seen how the consistency of M. Quraish Shihab in interpreting the poorest and his efforts to devise solutions to these realities.